An applied general equilibrium analysis of fiscal reforms to fight poverty in Mexico - Núñez Rodríguez, Gaspar; Polo Andrés, Clemente (Universidad Autónoma de Nuevo León, 2008)
The main goal of this paper is to analyze the consequences of two alternative ways of raising funds to finance poverty alleviation programs in Mexico: A Value Added Tax (VAT) reform and a personal income tax reform (IT). The impact of the reforms is analyzed with an applied general equilibrium model of the Mexican economy, calibrated using a 1996 Social Accounting Matrix. The model includes 18 production sectors, 10 representative households, the government, and the rest of the world. The cash transfers required to attain a fixed increase in the Equivalent Variation (EV) of the lowest income households are obtained either increasing effective VAT rates or IT rates. When all rates are scaled up by the same factor, the VAT reform generates a positive global EV considerably larger than the one obtained scaling the IT rates, though the latter diminishes (increases) lower (higher) income households’ contribution. Setting a uniform VAT rate results in a positive global EV considerably larger than the one obtained with a uniform IT. Moreover, the distribution gap increases in the latter case since the richest households receive the largest benefits. Clasificación JEL: D58, I32, I38.